Cytokinin and Ethylene Cell Signaling Pathways from Prokaryotes to Eukaryotes - Baptiste Bidon; Samar Kabbara; Vincent Courdavault; Gaëlle Glévarec; Audrey Oudin; François Héricourt; Sabine Carpin; Lukáš Spíchal; Brad M. Binder; J. Mark Cock; Nicolas Papon (Cells, 2020)
Cytokinins (CKs) and ethylene (ET) are among the most ancient organic chemicals on Earth. A wide range of organisms including plants, algae, fungi, amoebae, and bacteria use these substances as signaling molecules to regulate cellular processes. Because of their ancestral origin and ubiquitous occurrence, CKs and ET are also considered to be ideal molecules for inter-kingdom communication. Their signal transduction pathways were first historically deciphered in plants and are related to the two-component systems, using histidine kinases as primary sensors. Paradoxically, although CKs and ET serve as signaling molecules in different kingdoms, it has been supposed for a long time that the canonical CK and ET signaling pathways are restricted to terrestrial plants. These considerations have now been called into question following the identification over recent years of genes encoding CK and ET receptor homologs in many other lineages within the tree of life. These advances shed new light on the dissemination and evolution of these hormones as both intra- and inter-specific communication molecules in prokaryotic and eukaryotic organisms.